Assessment system for mathematics - B - Nor Fadilah Mohd Affandi. (2013)
Education has become one of the main concerns in this rapid moving technology world. In Singapore especially, the education system has always been the top priority. Singapore is constantly improving its education curriculums to enhance the students’ creativities and knowledge with the latest technology. Most of the assessment books available in the current market are hardcopy. Therefore, the questions are usually limited as it does not have the flexibility of changing the question dynamically.